Ultrafast Synthesis of Wavy Gold‐Silver Alloy Nanowires with Tunable Diameters in the Range of 2‐10 nm via a Seed‐Mediated Co‐Reduction. Issue 12 (23rd February 2021) - Wu, Quansen; Zhang, Gongguo; Ma, Yanyun; Li, Mengfan; Liu, Feng; Huang, Hongwen; Liu, Maochang; Zheng, Yiqun
Abstract: We report an ultrafast synthesis of wavy gold‐silver (AuAg) nanowires with tunable diameters via a seed‐mediated co‐reduction. The success of current strategy relies on the use of an elevated reaction temperature to accelerate the synthesis to be completed within several minutes and the use of Au seeds with controlled sizes to enable the manipulation over their diameters in the range of 2–10 nm. The presence of chloride‐contained quaternary ammonium surfactant and excessive reductant have been demonstrated to be critical for the high‐yield formation of AuAg products with the unique morphology of wavy nanowire. Due to the advantage in size control, the size effect on the plasmonic behavior of AuAg alloy wavy nanowires is investigated, where the products with sub‐5 nm diameter exhibit a broad shoulder absorbance peak in their spectrum. Abstract : Wavy gold‐silver alloy nanowires with tunable diameters in the range of 2–10 nm are prepared via an ultrafast seed‐mediated co‐reduction. Their UV‐vis extinction spectra show a broad absorbance band in the range of 450–550 nm.